Safe space online: the construction of intersectional safety in a South African feminist Facebook group - Roux, Kayla (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies, 2017)
In this thesis I investigate the construction of an intersectional 'safe space' in a closed South African feminist community on the social networking site Facebook. Drawing on my own experience as a group member, observations of group dynamics, focus group interviews with administrators, and interviews with past and present members, I discuss the practices and guidelines employed to ensure the safety and intersectionality of the group. This research spans a period of more than two years, and there were a number of developments in the group over this time. It is a relatively large and well-established feminist Facebook group in South Africa which enforces an intersectional approach to social justice, and it is explicitly formulated and closely monitored so that marginalised voices are privileged in group interactions. Despite the best efforts of group moderators, however, interactions between the privileged and the marginalised tend to reproduce existing power inequalities and jeopardise the safety of those the group is meant to serve. Although some interview participants feel that safe space practices such as the call-out system and exclusionary groups and posts serve to fragment the group and cause conflict, these complaints mainly originate from white women who were required to acknowledge their unearned privilege. Their presence in the group and the problem of 'white derailment' makes the space feel unsafe for many POC. Ultimately, a splinter group exclusively for POC was formed in order to provide a safer space for feminists of colour to find solidarity and support, discuss issues affecting them, and do the important and necessary work of selfdefinition. I conclude that while these spaces are limited - and absolute safety can never be guaranteed - these exclusive spaces are an integral starting point in the development of a transversal intersectional politics of solidarity between different actors and movements that share the same values.
Keywords: Uncatalogued